Answer:
A.
[tex](4x^3)^3[/tex]
C.
[tex](-0.2b^2)^3[/tex]
D.
[tex]\left(-\dfrac{2}{3}a^5\right)^3[/tex]
Step-by-step explanation:
A. Given [tex]64x^9.[/tex]
Note that
[tex]64=4^3\\ \\x^9=(x^3)^3,[/tex]
then
[tex]64x^9=4^3\cdot (x^3)^3=(4x^3)^3[/tex]
C. Given [tex]-0.008b^6.[/tex]
Note that
[tex]-0.008=(-0.2)^3\\ \\b^6=(b^2)^3,[/tex]
then
[tex]-0.008b^6=(-0.2)^3\cdot (b^2)^3=(-0.2b^2)^3[/tex]
D. Given [tex]-\frac{8}{27}a^{15}.[/tex]
Note that
[tex]-\dfrac{8}{27}=-\dfrac{2^3}{3^3}=\left(-\dfrac{2}{3}\right)^3\\ \\a^{15}=(a^5)^3,[/tex]
then
[tex]-\dfrac{8}{27}a^{15}=\left(-\dfrac{2}{3}\right)^3\cdot (a^5)^3=\left(-\dfrac{2}{3}a^5\right)^3[/tex]